Highly Selective Optical‐Electrochemical Zn2+ Detection Based on Tetrathiafulvalene. Issue 1 (30th November 2012) - Xiao, Xunwen; He, Yanjun; Wang, Guannan; Shen, Liangjun; Guo, Yuping; Fang, Jianghua; Yang, Jianping
ABSTRACT Ethylenedioxytetrathiafulvalene substituted with a pyridinyl (Py) group (1) shows remarkable sensing and coordinating properties only to Zn2+ ion, not to the other metal ions. Addition of a micromolar concentration of Zn2+ ion to the solution of 1, a dramatic change is observed in the UV–vis absorption spectrum and redox property, and the discrimination is readily possible even by "the naked eye." Comparison of the recognition ability between 1 and its reference compound (ethynylpyridinyltetrathiafulvalene) 2 suggests that the nature of the space linking tetrathiafulvalene and acceptor moiety plays an important role in the intramolecular charge‐transfer state. © 2012 Wiley Periodicals, Inc. Heteroatom Chem 24:72–76, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/hc.21066